The combination of user experience evaluation method in asessing the application of suicide risk idea identification - Tenia Wahyuningrum; Gita Fadila Fitriana; Dyah Wahyuningsih (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The global pandemic COVID-19 has led to extreme loss of human life worldwide. The pandemic has made a profound impact on the psyche of some people, and it has led to suicide. The need for confident handling of specific risk factors for suicide is needed. Therefore, to support Indonesian governments to control the increment of suicidal ideas for adolescents using a combination of unmoderated remote usability testing (URUT) and usability metric for user experience (UMUX)-Lite. Then we adopted the school-based mental health program to make a prototype mobile application using the risk factor for suicidal ideation (RFSI) instrument to identify suicidal ideas in adolescents. Participants’ characteristics included late adolescents aged 19-22 years, male and female. The results show that the time-based efficiency on the registered task obtained from the calculation is 0.025 goals/sec. In one second, participants could complete a 0.025 of the job; although all participants could complete all tasks well and quickly, they provided good satisfaction scores. Some design improvements are needed on the prototype by considering user input.